One Stop Service (OSS) Implementation Analysis In the Human Resource Development and Staffing Agency (BKPSDM) of Jambi City - Putra, Firmansyah; Hapsa, Hapsa; Saadah, Maratun (Jurnal Politik Indonesia: Indonesian Political Science Review, 2021)
This study analyzes the implementation of One-Stop Service (OSS) or integrated services in the Personnel and Human Resources Development Agency (BKPSDM) Jambi City. OSS is an alternative public service that is considered capable of answering several public services problems for both external and internal government organizations. This research uses a qualitative method, collecting primary and secondary data. The data analysis was carried out by qualitative descriptive, meaning that the collected data was filtered and then analyzed descriptively by the team until a conclusion was obtained regarding the issues found. This study indicates that, since it was implemented for the internal Jambi City Government employees in 2018, OSS at BKPSDM has provided satisfaction to employees. This sense of satisfaction indirectly impacted employees' service performance in all lines of public services in Jambi City. This indirect impact can be seen through the effectiveness of the services and the achievement of the service objectives. This study democratically provides essential public service delivery in Jambi City. This study emphasized in putting the customer first, providing service democratically instead of adopting many e-government innovations.